Telomerase Reverse Transcriptase and Telomerase RNA Component Gene Expression as a Novel Biomarkers for Alzheimer’s disease: Telomerase Gene Expression Levels as Novel Biomarkers of Alzheimer - Yashooa, Raya Kh.; Nabi, Ari Q. (Cellular and Molecular Biology, 2022)
Alzheimer’s disease (AD) is a neurological, age-related condition that causes cognitive decline and memory loss; it induces dementia in the elderly. Telomerase is a reverse transcriptase ribonucleoprotein that adds nucleotides to the end of DNA. This study aimed to compare human telomerase reverse transcriptase (hTERT) and telomerase RNA component (TERC) expression in different phases of AD and healthy cohorts. Sixty participants were divided into 30 who had dementia and 30 who did not. After collecting blood samples, total RNAs were extracted from the plasma. Screening for hTERT and TERC gene expression was carried out by quantitative reverse transcriptase real-time polymerase chain reaction (RT-qPCR) using the relative quantification method to estimate the expression changes in hTERT and TERC. The RT-qPCR results show that hTERT and TERC gene expression was significantly down-regulated in Alzheimer’s patients compared to the health subjects (P-value= <0.0001,0.005), respectively. The area under curve AUC was 0.773 for hTERT and 0.703 for TERC. The Mini-Mental State Examination scores revealed a significant difference between dementia and non-dementia subjects (P=<0.0001). We conclude down-regulations in both hTERT and TERC gene expression in AD patients, which supports our hypothesis that the telomerase expression gene in the blood of AD patients can serve as a non-invasive, early, and novel diagnostic marker of AD.